Diffusion Tensor Imaging for Quantitative Evaluation of Lumbar Intervertebral Disc Degeneration. (May 2014) - Oikawa, Y.; Eguchi, Y.; Watanabe, A.; Orita, S.; Yamauchi, K.; Suzuki, M.; Sakuma, Y.; Kubota, G.; Inage, K.; Sainoh, T.; Sato, J.; Fujimoto, K.; et al.
Introduction: Pfirrmann classification, T2- and T1ρ mapping using MRI are tools to evaluate intervertebral disc (IVD) degeneration. Diffusion tensor imaging (DTI) and diffuion tensor tractography (DTT) are neuroimaging tools for visualizing highly anisotropic tissues. Recently, DTI is used for evaluation of degenerated IVDs. The purpose of this study is to provide evidence for the efficacy of DTI and DTT in the quantitative evaluation of degenerated IVDs. Materials and Methods: Three patients with discogenic low back pain underwent DTI and DTT on a 3.0 T MR scanner. We evaluated 12 discs from L2-3 to L5-S in each patient. Pfirrmann classification on conventional MR imaging, fractional anisotropy (FA) value, morphological classification on DTT, and number of tracking fibers were evaluated. IVD was divided into three layers in a concentric manner from the center; FA value was measured at each layer. DTT was classified into ring, donut, and disk type. Results: With Pfirrmann classifications, six, two, and four discs were grades 2, 3, and 4, respectively. With DTT classification, six, one, and five discs were ring, donut, and disk types, respectively. All grades 2, 1, and3 discs corresponded to ring type, and all grade 4 and the other grade 3 discs corresponded to disk type. FA value of the intermediate layer was 0.10 for ring type, 0.21 for donut, and 0.23 for disk type. FA value of the inner layer was 0.06 for ring type, 0.09 for donut, and 0.20 for disk type. The number of tracking fibers was increased in disk types. Conclusion: This study showed that shape on DTT correlated to Pfirrmann classification, and DTT of discs can describe the IVD degeneration process. A previous study showed that water content tended to decrease in IVD degeneration. The increasing FA value and number of the tracking fibers may reflect a decreased water content and tissue degeneration. Thus, DTI and DTT can visualize and quantitatively evaluate IVD degeneration. DTI and DTT may detect degeneration and evaluate repair and regeneration. Disclosure of Interest None declared